Mutual causal effects between immune cells and hepatocellular carcinoma: a Mendelian randomization study - Zheng Wang; Mengshu Pan; Jie Zhu; Changhong Liu (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC), a malignant tumor that seriously endangering health, has aroused widespread concern in the field of public health. Previous researches have noted the relationships between immune cells and HCC, but the causal relationship was uncertain. Methods In this study, a bidirectional two sample Mendelian randomization (MR) analysis was utilized to access the causal relationship between immune cell characteristics and HCC. According to the open-access data, we investigated the causal relationship between 731 immune cell characteristics and HCC risk. Results After screening by IVW approach, increased levels of 8 immune traits and reduced levels of 7 immune traits could lead to changes in HCC risk. These 15 immune cells were distributed in the Monocyte (4 cells), Treg panel (4 cells), TBNK (3 cells), Maturation stages of T cell panel (3 cells), and cDC panel (1 cells). Furthermore, HCC was identified to have causal effects on 21 immunophenotypes. Among these immune cells, hepatocarcinogenesis had the greatest impact on CD4 on EM CD4 + and CD33 on Mo MDSC. Conclusions This study enhances our comprehension of the interaction between immune cells and HCC risk, furnishing novel avenues to explore the mechanisms of HCC.